The PARTICIPATION IN JOB LOSS SECURITY PROGRAM AS UNEMPLOYMENT BENEFIT FOR NON WAGE RECIPIENT PARTICIPANT: Bahasa Indonesia - Agusmidah, Agusmidah; Reynaldo, Vatar (Fakultas Hukum Universitas Jambi, 2024)
The establishment of a Job Loss Security Program in The Stipulation of a Government Regulation instead of Law Number 2 Year 2022 concerning Job Creation protects workers who have experienced the severance of employment relationship. This form of protection, by International Labor Organization Convention 102 and Convention 168, is known as Unemployment Benefits. The Unemployment Benefit Scheme in Indonesia is implemented through the Job Loss Security Program. In its regulation under Article 45A of Law Number 50 Year 2004 concerning the National Social Security System in conjunction with the Job Creation Law, the Job Loss Security Program only provides benefit protection to workers who experience severance of employment, in other words, to workers with employment relationships who are Wage Recipients Participants in the BPJS membership. The protection of the Job Loss Security Program to non-wage recipient participants in BPJS membership, consisting of workers outside of employment relationships, is still not covered due to the limitation of beneficiary rules only to workers who experience severance of employment relationships. The research method used is a normative juridical method with a descriptive nature. This study shows that the existing regulations only provide partial protection. Countries such as Denmark, Spain, Serbia, the People's Republic of China, and others have previously implemented mandatory or voluntary Unemployment Benefit schemes for non-employment relationship workers. In this study, these countries serve as a comparison for the Unemployment Benefit system between developed and developing countries that have implemented it beforehand. The Unemployment Benefit system previously applied to non-employment relationship workers in other countries is an opportunity for Indonesia to implement it as well. The urgency of Unemployment Benefits Social Security protection through the Unemployment Benefits Program is important as a form of state protection holistically.